Persistent oseltamivir-resistant pandemic influenza A/H1N1 infection in an adult with cystic fibrosis. (26th April 2011) - Flight, William George; Bright-Thomas, Rowland; Mutton, Kenneth; Webb, Kevin; Jones, Andrew
Abstract : The authors report the case of a 25-year-old patient with cystic fibrosis (CF) who developed pandemic influenza A/H1N1 during a visit to the USA in August 2010. The patient has severe CF lung disease and takes maintenance oral corticosteroids. The influenza virus was positive for the H275Y oseltamivir-resistance mutation despite the patient never having received oseltamivir. The patient has remained sputum-positive for over 4 months despite inhaled zanamivir therapy. This is the first reported case of transmission of oseltamivir-resistant H1N1 influenza to a patient with CF. The frequency of prolonged sputum carriage of pandemic influenza and transmission of oseltamivir-resistant strains are unknown on a population level. However, if our observations are replicated in other CF patients, they are potentially of considerable importance to clinical and infection-control practices in this patient group.